1988
DOI: 10.1210/endo-122-5-2285
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Effects of Vanadate in Isolated Rat Adipocytes*

Abstract: Vanadate has been shown to have a number of insulin-like effects in various cells, including isolated rat adipocytes. In the present study we compared the activities of vanadate and insulin in isolated fat cells using a number of different assays of insulin-like activity. Both insulin and vanadate stimulated [2-3H]glucose incorporation into fat cell lipid in a dose-dependent manner, but the maximal effect of vanadate was markedly greater than that of insulin. At 10(-2) M vanadate the effect was 3-4 times as gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
1
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(50 citation statements)
references
References 18 publications
2
46
1
1
Order By: Relevance
“…Among the four complexes, VU-MPA was found to have the highest partition coefficient. Effect of vanadyl complexes on FFA release from isolated rat adipocytes treated with epinephrine To evaluate in vitro insulin mimetic activity of four vanadyl complexes, we examined the effect of these complexes on FFA release from isolated rat adipocytes treated with epinephrine in the absence of glucose as proposed before [16,22,28,38,39]. Figure 2 summarizes the effects of the four vanadyl complexes, comparing with that of VS as a positive control.…”
Section: Resultsmentioning
confidence: 99%
“…Among the four complexes, VU-MPA was found to have the highest partition coefficient. Effect of vanadyl complexes on FFA release from isolated rat adipocytes treated with epinephrine To evaluate in vitro insulin mimetic activity of four vanadyl complexes, we examined the effect of these complexes on FFA release from isolated rat adipocytes treated with epinephrine in the absence of glucose as proposed before [16,22,28,38,39]. Figure 2 summarizes the effects of the four vanadyl complexes, comparing with that of VS as a positive control.…”
Section: Resultsmentioning
confidence: 99%
“…These include enhancement of glucose transport and oxidation in rat adipocytes [17,18] and skeletal muscle [19,20], stimulation of pentose phosphate pathway [21] and glycogen synthase activity in rat adipocytes [22], enhancement of glycogen synthesis in the liver and diaphragm [23], inhibition of lipolysis [24] and activation of lipogenesis in rat adipocytes [25] and reduction of insulin requirement in spontaneously diabetic (BB Wistar) rats [26]. It has also been shown that vanadium compounds, both in the vanadate and vanadyl forms, lower plasma glucose and prevent the decline in cardiac performance [26][27][28][29][30] due to diabetes when administered to intact experimentally-induced diabetic rats.…”
mentioning
confidence: 99%
“…If left untreated, DM can lead to a complication of diabetes. It is well known that vanadium compounds have insulin-like effects in vivo [1][2][3][4][5][6][7][8] and in vitro [9,10], but medicinally-useful vanadium compounds have not yet been developed. One of reasons is that vanadium is cytotoxic at high concentrations.…”
Section: Introductionmentioning
confidence: 99%